Analisis Potensi Timbulan dan Jenis Sampah Elektronik Rumah Tangga di Kota Administrasi Jakarta Pusat - Sifa Nurhidayati; Gina Lova Sari; Venny Ulya Bunga (Journal Serambi Engineering, 2024)
This study aims to identify the generation and potential of household electronic waste in the Central Jakarta Administrative City. E-waste, which falls under the category of hazardous and toxic waste (B3), consists of used electronics that are discarded because they are no longer in use. Based on data from the Ministry of Environment and Forestry (KLHK) in 2021, Indonesia will generate around 2 million tonnes of e-waste, 56% of which will come from the island of Java. E-waste management in Indonesia is still sub-optimal, with only 17.4% being properly managed. This study involved 100 households in Central Jakarta through observation, interviews and questionnaires. The data was analysed using a qualitative descriptive approach. The results showed that washing machines, refrigerators, and air conditioners are the most common types of household e-waste, with estimated generation of 571,038.11 kg/year, 514,299.67 kg/year, and 475,904.09 kg/year, respectively. Projections show that the generation of e-waste will increase every year as the population grows.